Management Systems of the Quality of Studies - Ruževičius, Juozas (Ekonomika, 2007)
The aim of this study is to show the importance of quality in the economics and social field and to highlight the peculiarities, problems and interferences of education quality assurance at universities and colleges. The article is prepared using the scientific and methodological literature together with organizations’ research. case-study analysis and summary of education practice at universities and colleges of Lithuania and in the world. The implementation of the TOM and ISO 9001 systems at universities and colleges provides for the following benefits: personnel involvement into the processes of education quality improvement; better usage of personnel competency; more precise measurement and assessment of work results; better identification and control of processes; rise of satisfaction of clients, social partners and society with work results of universities. Most of education institutions implementing quality management tools and principles confront the following major problems: complicated description of the study quality concept and content; multiplicity of study quality indicators and their measurement and assessment vulnerability; lack of skills using the TOM concept, its principles, ISO 9001 management models and quality methods; difficulties in resolving university work into interdependent managed the processes and the process of thinking development; inertia and sometimes even resistance of part of the employees to fundamental changes. An original model of the organization development “tree” is presented.